HUBUNGAN POSISI PERGELANGAN TANGAN SAAT MENGETIK TERHADAP RISIKO TERJADINYA CARPAL TUNNEL SYNDROME: STUDI LITERATUR - Abdurahman Berbudi B L; Farida Ariyanti; Erna Sariana (Jurnal Fisioterapi dan Kesehatan Indonesia, 2022)
Background: The use of computers has a high risk of experiencing wrist trauma disorders, namely the occurrence of carpal tunnel syndrome, which is caused by compression of the median nerve at the wrist and causes joint pain. This is influenced by years of activity in using a keyboard and mouse on a computer. Ergonomic position on the wrist when using the keyboard and mouse while typing is an important thing to prevent the occurrence of carpal tunnel syndrome. Objective: This study aims to analyze the results of previous studies regarding the relationship between wrist position when typing and the risk of carpal tunnel syndrome. Research Methods: The design used is a literature study. By searching through search engines, namely PubMed, Google Scholar, PMC, and Semantic Scholar. Results: Obtained 6 eligible literatures. Overall, the literature shows a significant relationship between wrist position while typing and the risk of developing carpal tunnel syndrome. Conclusion: Ergonomic position on the wrist when using the keyboard and mouse when typing is an important thing to prevent carpal tunnel syndrome..